Dynamics of Experience in a Learning Protocol: A Case Study in Climbing - Rochat, Nadège; Hacques, Guillaume; Ganière, Caroline; Seifert, Ludovic; Hauw, Denis; Iodice, Pierpaolo; Adé, David (Frontiers in Psychology, 2020)
Many of the studies on motor learning have investigated the dynamics of learning behaviors and shown that the learning process is nonlinear, self-organized and situated. Aligned with this research trend, studies within the enactive paradigm focus on learners’ lived experience to understand how it shapes their intentions, actions and perceptions. Thus, a joint analysis of experiential and behavioral assessments might help to explain the dynamics of learning (e.g., the transition between stable states). The aim of this case study was to analyze the dynamics of a beginner climber’s lived experience as his performance progressed (i.e., climbing fluency) during a learning protocol. The protocol comprised ten climbing sessions over five weeks. During the sessions, the climber had to climb a “control route” (i.e., a route that never changed) and “variants” (i.e., novel routes, in which the spatial layout of the holds was modified). Phenomenological data were collected with self-confrontation interviews after each session. From the verbalizations, a thematic analysis of the climber’s intentions, actions and perceptions was performed to detect the general dimensions of his experience. The behavioral data (the climber’s performance) were assessed using four indicators of climbing fluency: climbing time, immobility ratio, geometric index of entropy of the hip trajectory, and the jerk. Our results highlighted the dynamics of the climber’s lived experience and performances in the unchanged and novel environments. The dynamics on the control route were characterized by four crucial episodes and the dynamics on the variants, by four ways of experiencing novelty. Our results are discussed around three points: (i) the climber’s definition of his enacted fluency in terms of intentions, actions, and perceptions; (ii) how the definition was identified through a dynamic phenomenological synthesis; and (iii) three effects that characterize the dynamics: challenge, metaphor and a refinement in perceptions.